A CNN Based Method for Detecting Covid-19 from CT Images - Kaya, Buket; Önal, Muhammed (Ali KARCI, 2021)
COVID-19 outbreak first emerged on December 31, 2019 in Wuhan, China. The Novel Coronavirus Disease is caused by the SAR-CoV-2 virus, which causes respiratory symptoms such as fever, cough, and shortness of breath. While scientists continue their fight against SARS-CoV-2 (2019-nCoV), one of the deadliest viruses in the last century, with tests to help diagnosis and prognosis, drug and vaccine discovery, Information Technologies mostly continues to work on early diagnosis, prognosis and prediction. The aim is to reveal systems with low margin of error that will alleviate the workload of healthcare professionals, as well as early diagnosis and initiation of treatment.Deep Learning and Computer vision is the most commonly used. Two class (covid, non-covid) classification solution, using the Artificial Intelligence Techniques, have been examined in this paper. CNN architecture, has been created to develop an model to disease detection process of COVID-19(2019-nCoV) virus infected patients from CT images consisting of NON-COVID and COVID classes. We have proposed the classifying of CT images using the 2 Convolutions and pool layers with the model which shortening the time for classification and achieved an accuracy of nearly 95.77%. Results show that the used model attains provide highly satisfying results and can be used for any image classification.

COVID-19 salgını ilk olarak 31 Aralık 2019'da Çin'in Wuhan kentinde ortaya çıktı. Yeni Koronavirüs Hastalığına ateş, öksürük ve nefes darlığı gibi solunum semptomlarına neden olan SAR-CoV-2 virüsü neden olur. Bilim insanları, son yüzyılın en ölümcül virüslerinden biri olan SARS-CoV-2 (2019-nCoV) ile tanı ve prognoza yardımcı olacak testler, ilaç ve aşı keşfi ile mücadelelerini sürdürürken, Bilgi Teknolojileri de çoğunlukla erken teşhis konusunda çalışmalarını sürdürüyor. Amaç, sağlık çalışanlarının iş yükünü hafifletecek, erken teşhis ve tedaviye başlamayı sağlayacak, hata payı düşük sistemleri ortaya çıkarmaktır. Bu makalede, Yapay Zeka Teknikleri kullanılarak iki sınıflı (covid, covid olmayan) sınıflandırma çözümü incelenmiştir. CNN mimarisi, COVID-19(2019-nCoV) virüsü ile enfekte hastaların, KOVİD OLMAYAN ve COVID sınıflarından oluşan BT görüntülerinden hastalık tespit sürecine bir model geliştirmek için oluşturulmuştur. Sınıflandırma süresini kısaltan ve yaklaşık %95.77 doğruluk sağlayan model ile BT görüntülerinin 2 Konvolüsyon ve havuz katmanları kullanılarak sınıflandırılmasını önerdik. Sonuçlar, kullanılan modelin oldukça tatmin edici sonuçlar verdiğini ve herhangi bir görüntü sınıflandırması için kullanılabileceğini göstermektedir.
CT Görüntülerinden Covid-19 Tespiti için CNN Tabanlı Bir Yöntem
Keywords: Artificial Intelligence; Yapay Zeka